2006
DOI: 10.1007/s10566-005-9003-6
|View full text |Cite
|
Sign up to set email alerts
|

Experiential Learning Strategies for Promoting Adolescents’ Voluntarism in Hong Kong

Abstract: Nurturing adolescents' voluntarism-their willingness to help needy strangers-appears to hinge on the experiential learning component embedded in a volunteer training program. Evidence for this is presented from an experimental study carried out in Hong Kong. Although program participants did not differ in voluntarism from their classmates who did not participate in the program, those who devoted more time to volunteer services were ultimately significantly higher on voluntarism. Those who volunteered for servi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…They were both popular program approaches used by social workers working with adolescents and young people in Hong Kong. Both of them ground their theoretical base in the experiential learning theory [9,13,14]. The Type C program has a much longer history that dates back to the late 1960s and has since been a popular program, while Type B was formally adopted as the major program theory for a huge social intervention program entitled "The Understanding the Adolescent Project" (UAP) designed to combat the problems among students identified as adolescents-at-risk from 2001 to 2004 in Hong Kong [3,15] It is noteworthy that although the ABC approach and volunteer training and services are popular programs offered by social workers in Hong Kong, the effectiveness of these programs has not been properly documented.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They were both popular program approaches used by social workers working with adolescents and young people in Hong Kong. Both of them ground their theoretical base in the experiential learning theory [9,13,14]. The Type C program has a much longer history that dates back to the late 1960s and has since been a popular program, while Type B was formally adopted as the major program theory for a huge social intervention program entitled "The Understanding the Adolescent Project" (UAP) designed to combat the problems among students identified as adolescents-at-risk from 2001 to 2004 in Hong Kong [3,15] It is noteworthy that although the ABC approach and volunteer training and services are popular programs offered by social workers in Hong Kong, the effectiveness of these programs has not been properly documented.…”
Section: Discussionmentioning
confidence: 99%
“…This paper presents and discusses the findings of an outcome evaluation of the Tier 2 Program implemented in the Full Implementation Phase (FIP) of the Project in 2007/08 based on the perspective of the participants. Two similar studies were conducted to evaluate the Tier 2 Program implemented in three cohorts: (1) the Experimental Implementation Phase (EIP) of the project in 2005/06 (3,072 Secondary 1 students in 52 schools); (2) EIP in 2006/07 (2,542 Secondary 2 students in 49 schools); and (3) FIP in 2006/07 (13,194 Secondary 1 students in 207 schools [4,5]. Both studies found that roughly four-fifths of the respondents of the three cohort studies regarded the program as helpful to them.…”
Section: Introductionmentioning
confidence: 99%
“…They were both popular program approaches used by social workers working with adolescents and young people in Hong Kong. Both of them ground their theoretical base in the experiential learning theory [6,10,11]. The Type C program has a much longer history that can date back to the late 1960s and has since been a popular program, while Type B was formally adopted as the major program theory for a huge social intervention program entitled "The Understanding the Adolescent Project" (UAP) to combat problems among students identified as adolescent-at-risk from 2001 to 2004 in Hong Kong [12,13].…”
Section: Discussionmentioning
confidence: 99%
“…They were both popular program approaches used by social workers working with adolescents and young people in Hong Kong. Both of them ground their theoretical base in experiential learning theory [23,24,25]. The VTS element only program has a much longer history that can date back to the late 1960s and has since been a popular program, while the ABC only program was formally adopted as the major program theory for a huge social intervention program entitled -The Understanding the Adolescent Project‖ (UAP) to combat problems among students identified as adolescent-at-risk from 2001 to 2004 in Hong Kong [26,27].…”
mentioning
confidence: 99%